Non-cell-autonomous mechanisms of tumor initiation and relapse by chromosomal instability - Simona J. A. Lafirenze; Bastiaan van Gerwen; Ajit I. Quirindongo; Natasja Costermans; Aniek Janssen; Banafsheh Etemad; Pim Toonen; Marco A. D. Louro; Wilma H. M. Hoevenaar; Sameh Youssef; Alain de Bruin; Lodewijk A. A. Brosens; et al. (Proceedings of the National Academy of Sciences, 2026)
Chromosomal instability (CIN) is a hallmark of cancer, and a primary cause of genetic heterogeneity in tumors. Depending on the degree of CIN and the affected tissue, CIN can promote or suppress tumor formation, and high CIN induction has been proposed as a therapeutic strategy. How CIN achieves these effects is unclear. Here we use a conditional mouse model of graded CIN in combination with longitudinal monitoring of DMBA/TPA-initiated skin tumors to show that low CIN increases the frequency of skin tumor initiation, while higher CIN accelerates tumor onset and growth rates. Strikingly, gene recombination analysis of the tumors reveals that upon high CIN induction the fast-growing tumors originate from rare low CIN cells, suggesting a strong non-cell-autonomous effect of high CIN. Gene expression analysis and immunohistochemistry show that high CIN causes epidermal hyperplasia, immune evasion, and a regenerative response that stimulates low CIN tumor growth beyond what is achieved by induction of low CIN alone. Such cell-extrinsic effects may be a common mechanism of tumor formation by CIN, as we observe it also in CIN-induced tumors of the intestine, breast, and mesentery. When high CIN is induced in established skin tumors, mimicking CIN-based therapy, tumors regress but relapse quickly. Relapsed tumors, too, arose from rare low CIN cells. Our findings have implications for our understanding of the contributions of CIN to cancer initiation and progression and give caution to the rationale for CIN therapies.